Introduction of brick (9.5”×4.5”×2.75”) (RFA-262_Rev B) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of PDF version of drawings.